The Effect of BIM Use on the Effectiveness of Knowledge Management in SOE Contractors with ISO 19650 BIM - Utama, Singgih Fitra; Sari, Ayu Fatimah; Sumardi, Sumardi (Civil and Environmental Science Journal (CIVENSE), 2026)
The implementation of Building Information Modeling (BIM) is increasingly being applied in construction projects, including by state-owned contractors who adopt the ISO 19650 standard as an information management framework. However, empirical evidence on the effect of BIM on the effectiveness of Knowledge Management (KM) among ISO 19650-based state-owned contractors remains limited. This study aims to analyze the impact of BIM implementation on the Knowledge Management process, the effectiveness of Knowledge Management, and the ability to overcome Knowledge Management obstacles. The study uses a quantitative approach with a 1–5 Likert-scale questionnaire survey of 114 respondents from SOE contractors. Data analysis was performed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The BIM variable focused on collaboration, while the KM variable covered key activities, including knowledge acquisition, documentation, storage, sharing, and utilization. The results showed that BIM implementation had a positive and significant effect on all KM variables. Specifically, BIM significantly influences the KM process (β = 0.897), KM effectiveness (β = 0.949), and the ability to overcome KM obstacles (β = 0.943), all at p < 0.001. In addition, the model has strong explanatory power, with R² values of 0.805 for the KM process, 0.901 for KM effectiveness, and 0.890 for overcoming KM obstacles. These findings indicate that the higher the implementation of collaboration-based BIM in accordance with ISO 19650, the more the KM process and effectiveness of state-owned contractors will increase, including in overcoming KM obstacles. This study provides practical implications for SOE contractors to strengthen their BIM implementation strategies to improve knowledge management performance in construction projects.